Preparation of Financial Statements of Non-Profit Organizations Based on ISAK 35 (Case Study on the Disaster Risk Reduction Forum of South Dolo District) - Rahma Aulia; Masruddin; Ni Made Suwitri Parwati; Rahma Masdar (GoodWill, 2025)
This study aims to analyze and prepare the financial statements of the Disaster Risk Reduction Forum (FPRB) of South Dolo District and evaluate their compliance with the financial reporting standards for non-profit organizations as stipulated in ISAK 35. The research employs a descriptive qualitative approach to obtain an in-depth understanding of the organization’s financial recording practices and the extent to which they align with applicable accounting standards. Data were collected through interviews with management, documentation of daily, weekly, and monthly financial transactions, and a literature review focusing on ISAK 35 as the primary reference for report preparation. The findings indicate that FPRB’s existing financial records are limited to basic cash inflow and outflow notes and have not yet met the minimum reporting components required for non-profit entities. Through the implementation of ISAK 35, this study successfully compiles a complete set of financial statements, including the statement of financial position, statement of comprehensive income, statement of changes in net assets, cash flow statement, and notes to the financial statements. The use of Microsoft Excel supports a more systematic preparation process and enhances the organization’s financial accountability. Overall, this research demonstrates that adopting ISAK 35 can improve the transparency, reliability, and comparability of financial information in small-scale non-profit organizations, particularly those engaged in disaster risk reduction. The study also highlights the need for capacity building to ensure consistent implementation of standardized financial reporting practices across similar entities.